2000
DOI: 10.1148/radiology.217.1.r00oc2789
|View full text |Cite
|
Sign up to set email alerts
|

Tunneled Infusion Catheters: Increased Incidence of Symptomatic Venous Thrombosis after Subclavian versus Internal Jugular Venous Access

Abstract: The IJV is the preferred site for tunneled infusion catheter placement because of the lower incidence of symptomatic venous thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
2
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 21 publications
5
93
2
5
Order By: Relevance
“…After they have been implanted, stents may migrate, and cardiac pacemaker wires. [2][3][4] One study found that 27% of patients with COVD had a previous history of catheters or pacemaker wires, 2 primarily in subclavian veins, in which the occurrence of the disease can reach 50%, in contrast with the internal jugular vein, in which the occurrence rate is 10%. 3 This prevalence was associated with the large caliber of hemodialysis catheters and the high flow rates of dialysis sessions.…”
Section: Discussionmentioning
confidence: 99%
“…After they have been implanted, stents may migrate, and cardiac pacemaker wires. [2][3][4] One study found that 27% of patients with COVD had a previous history of catheters or pacemaker wires, 2 primarily in subclavian veins, in which the occurrence of the disease can reach 50%, in contrast with the internal jugular vein, in which the occurrence rate is 10%. 3 This prevalence was associated with the large caliber of hemodialysis catheters and the high flow rates of dialysis sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Category IA C. No recommendation can be made for a preferred site of insertion to minimize infection risk for a tunneled CVC [61][62][63]. Unresolved issue D. Place catheters used for hemodialysis and pheresis in a jugular or femoral vein rather than a subclavian vein to avoid venous stenosis if catheter access is needed [259][260][261][262][263]. Category IA IV.…”
Section: Category Ib II Surveillancementioning
confidence: 99%
“…Such complications occur in 11-50 % of haemodialytic patients [1][2][3][4] . The most frequently quoted causes of stenosis or occlusion of the central venous system in such patients include acute and chronic trauma caused by the repeated punctures and cannulations of the subclavian veins 2,5,6 . Other causes in patients with shunt include hypercirculation accompanied by turbulencies, aggregation of thrombocytes and occurrence of thrombi leading to intima hyperplasia and fibrosis in the location of the original stenosis 1 .…”
Section: Introductionmentioning
confidence: 99%